2015
DOI: 10.1016/j.ssresearch.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Foreclosures and crime: A city-level analysis in Southern California of a dynamic process

Abstract: Although a growing body of research has examined and found a positive relationship between neighborhood crime and home foreclosures, some research suggests this relationship may not hold in all cities. This study uses city-level data to assess the relationship between foreclosures and crime by estimating longitudinal models with lags for monthly foreclosure and crime data in 128 cities from 1996 to 2011 in Southern California. We test whether these effects are stronger in cities with a combination of high econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Hipp also finds that, in cities where there were higher eviction rates, robbery and assaults increased. However, this association does not appear in all cities, though the effect was greater in cities with more economic inequality and low socioeconomic segregation (Hipp and Chamberlain, 2015).…”
Section: Resultsmentioning
confidence: 85%
“…Hipp also finds that, in cities where there were higher eviction rates, robbery and assaults increased. However, this association does not appear in all cities, though the effect was greater in cities with more economic inequality and low socioeconomic segregation (Hipp and Chamberlain, 2015).…”
Section: Resultsmentioning
confidence: 85%
“…In the wake of the housing crisis, a flurry of research has examined how foreclosures impact crime in communities. Recent scholarship has focused on the relationship between foreclosures and crime at the city, county, and neighborhood level yielding mixed results (Acevedo 2009;Cui 2010;Hipp and Chamberlain 2015;Katz, Wallace, and Hedberg 2013;Stucky, Ottensmann, and Payton 2012; Williams, Galster, and Verma 2014). However, the role of housing speculators has been largely unstudied in prior research, despite investors' significant role in the housing boom and bust (J. M. Lee and Choi 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Early research testing cross-sectional effects found mixed and contradictory results regarding the relationship between foreclosures and crime (see Acevedo 2009;Immergluck and Smith 2006;Kirk and Hyra 2012;Stucky, Ottensmann, and Payton 2012;Williams, Galster, and Verma 2014). Recent studies examining longitudinal effects show a more definitive link between neighborhood foreclosures and crime over time, although the nature of that time line, whether it is monthly, yearly, or longer, is in flux (Cui 2010;Ellen, Lacoe, and Sharygin 2013;Hipp and Chamberlain 2015;Katz, Wallace, and Hedberg 2013;Wallace, Hedberg, and Katz 2012;R. E. Wilson and Paulsen 2010).…”
Section: The Relationship Between Foreclosures and Crimementioning
confidence: 99%
See 2 more Smart Citations